(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2020)
The purpose of this article is to review the basic principles governing the evolution of the composition of the welding joint. The susceptibility to cracking of welded structures is a function of the microstructure, the environment, and the stresses applied; it is essential to understand the basic principles of the composition and evolution of the microstructure during welding. This article will focus primarily on fusion welding.